Herbal Medicinal Products from Passiflora for Anxiety: An Unexploited Potential - Lyca R. da Fonseca; Rafaele de A. Rodrigues; Aline de S. Ramos; Jefferson D. da Cruz; José Luiz P. Ferreira; Jefferson Rocha de A. Silva; Ana Claudia F. Amaral (The Scientific World Journal)
Herbal medicines containing Passiflora species have been widely used to treat anxiety since ancient times. The species Passiflora incarnata L. is included in many Pharmacopoeias, and it is the most used species in food, cosmetic, and pharmaceutical industries. However, there are around 600 species of the genus Passiflora and probably other species that can be used safely. Thus, this article was based on a search into the uses of the main species of the genus Passiflora with anxiolytic activity and its main secondary metabolites and some pharmacological studies, patents, and registered products containing Passiflora. Furthermore, the Brazilian Regulatory Health Agency Datavisa, Medicines and Healthcare Products Regulatory Agency of the United Kingdom, and the European Medicines Agency websites were consulted. The results showed that Passiflora species have health benefits but clinical trials are still scarce. The complexity of Passiflora extracts creates challenges for the development of herbal medicines. P. incarnata is the most studied species of the genus and the most used in natural anxiolytic herbal medicine formulations. However, there are hundreds of Passiflora species potentially useful for medicinal and nutraceutical purposes that are still little explored.